POSISIONING DAN SEGMENTASI HANDPHONE DENGAN MENGGUNAKAN PENDEKATAN PEMETAAN PERSEPSI - Alifah Ratnawati; Noor Kholis (Conference In Business, Accounting, And Management (CBAM), 2015)
The consumer’s perception in a product has a different from the company’s perception. The difference perception in a company will be appeared in the positioning and depends on segmentation’s product. The purpose of this research is to develop positioning and segmentation model based on the perception. If it perception can be mapped by the consumer and a company’s perception. Thus, these can be seen how positioning and segmentation’s product where these have different with the consumer to the company. It can be concluded that a company needs a reposition and segmentation to their product or not. The outcome of this target can be formed of consumer perception map to seven label phone. From this perception mapping will be able to be known how the positioning, segmentation, and consumer’s preference in a product. While from the research result which examined what perception mapping model that is produced appropriate with the objective conditions according to company. Therefore, it can be concluded what does the company needs repositioning or does not. The population  of this  research is  consumer  and  branch  manager  from  agency, distributor, and central selling market label such as Blackberry, Apple iphone, Nokia, Samsung, HTC, and Nexian in Semarang. Meanwhile, the approach that is used are descriptive analysis by using mapping perception method in graphic based on result analysis multi dimensional selling, and cluster analysis combine with descriptive analysis. The data is gotten by using mail survey to all respondent and deep interview to each respondent    Keywords : posisioning, segmentasi, preferensi, peta persepsi, handphone